Assessment of Tilawati Jilid Promotion at Darul Falah Lamandau Foundation Using the Profile Matching Method - Safitri, Diah Atika; Nurahman (Politeknik Dharma Patria Kebumen, 2021)
The assessment of tilawati jilid promotion refers to an activity performed to the students’ ability before they study the next jilid. This step is to determine the success of learning of the jilid. The research was carried out by applying the profile matching method to calculate the values by using the standard values. By using the Profile Matching method, the results were that 5 students were promoted to the next jilid and 2 students had to improve their ability. In the accuracy test, 7 test data were used based on the original test data and system test data. Based on the comparison, the 7 data had the same results as the original data. Therefore, the accuracy calculation obtained a rate of 100%.